A new species of Diostracus Loew, 1861 (Diptera: Dolichopodidae) from China with a key to species from the Yunnan Province - I.Ya. Grichanov (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2017)
Diostracus (Lagodechia) kabaki sp. n. from China is described. Diostracus filiformis Zhu, Masunaga, Yang, 2007 from Yunnan and D. nishiyamai Saigusa, 1995 from Guizhou, Hunan and Sichuan are associated with the subgenus Lagodechia Negrobov, et Tsurikov, 1996, and D. brevabdominalis Zhu, Masunaga, Yang, 2007 from Yunnan – with the subgenus Diostracus Loew, 1861. A key to species known from the Yunnan Province is provided